Epidemiological monitoring of congenital spinal hernia under conditions of anthropogenic load in the population of Belarus - Kokorina, Nadezhda V.; Malinovskaya, Yulia V.; Ershova-Pavlova, Alla A. (Journal of the Belarusian State University. Ecology, 2020)
The article presents the incidence of spinal hernias for the period from 2012 to 2016. It was established that the maximum population frequency of congenital spinal fungi in the Republic of Belarus was recorded in 2012 and have 1.01 ‰; in the Minsk and the Minsk region (2016) – 1.07 %. The effectiveness of prenatal diagnostics on average in the Republic of Belarus is 82.1 ‰, in the Minsk – 87.9 ‰, in the Minsk region – 83.1 ‰.
Keywords: congenital malformations; congenital spinal hernia; population frequency; teratogenic effects; prenatal diagnosis